Determinants of food insecurity among Syrian refugee women and their coping strategies - Kübra Esin; Feride Ayyıldız (BMC, 2024)
Abstract Aim There is limited knowledge on the prevalence, risk factors, and coping strategies of food insecurity among women refugees. The aim of this study was to determine the prevalence, severity, and risk factors of food insecurity among Syrian women refugees living in Türkiye (Turkey) and to evaluate the various coping strategies they use to manage food insecurity. Methods This descriptive cross-sectional study was conducted with 251 Syrian women refugees aged 18-64 years living in Türkiye. Data were collected by native Arabic-speaking researchers through online and face-to-face surveys. Sociodemographic data, anthropometric measurements, food insecurity status, and coping strategies were analyzed. 'Food Insecurity Experience Scale (FIES)' was used to determine the food insecurity status. Results It was found that 28% of the women who participated in the study had food security, 35% had mild, 24% had moderate, and 13% had severe food insecurity. In the group with food insecurity, age, number of children in the family, and average body mass index (BMI) were higher, while education and income level were lower (p < 0,05). For each 1-unit increase in BMI, there was a 0.122 increase in the total FIES score. A 1-unit increase in the number of children was associated with a 0.333 increase in the total FIES score. The most preferred strategies to cope with food insecurity were found to be purchasing less preferred and cheaper foods, and reducing portion sizes. Conclusion It was found that food insecurity is common among Syrian women refugees living in Türkiye. Women who are older, have more children, lower income, lower education, and higher BMI are more likely to experience food insecurity. Studies with larger samples and longer follow-up periods are needed to investigate the causes and effects of food insecurity among women refugees.